Laser cutting in marquetry leather: the design process with reuse of waste (ModaPalavra e-periódico, 2016)
The objective of this study was to present the marquetry process, with the use of laser cutting technology, applied to leather waste to develop fashion design products. This work was developed from the case study of Brantê brand, whose data were collected through observation and informal interviews. At the end of the study, it was found that the marquetry leather with the use of laser cutting is a process that can be applied to various kinds of products; also it realized that the products developed by Brantê get prominence in the market because they have aesthetic and symbolic value resultant of a distinctive design process. The reuse of leather also contributes to the result achieved by the company in the market, once the process is suitable to the standards of the products developed, according to quality criteria for reuse of a material discarded earlier.
Keywords: leather waste; laser cutting technology; fashion products